An Integrated All-Atlantic Ocean Observing System in 2030 - deYoung, Brad; Visbeck, Martin; de Araujo Filho, Moacyr Cunha; Baringer, Molly O’Neil; Black, CarolAnne; Buch, Erik; Canonico, Gabrielle; Coelho, Paulo; Duha, Janice T.; Edwards, Martin; Fischer, Albert; Fritz, Jan-Stefan; et al. (Frontiers in Marine Science, 2019)
The ocean plays a vital role in the global climate system and biosphere, providing crucial resources for humanity including water, food, energy and raw materials. There is a compelling need to develop an integrated basin-scale ocean observing system to support of ocean management. We articulate a vision for basin-scale ocean observing - A comprehensive All-Atlantic Ocean Observing Systems that benefits all of us living, working and relying on the ocean. Until now, basin-scale ocean observation has been conducted through loosely-aligned arrangements of national and international efforts. The All-Atlantic Ocean Observing System (AtlantOS) is an ntegrated concept for a forward-looking framework and basin-scale partnership to establish a comprehensive ocean observing system for the Atlantic Ocean as a whole. The system will be sustainable, multi-disciplinary, multi-thematic, efficient, and fit-for-purpose. Platforms, networks, and systems do already exist that operate at various maturity levels. AtlantOS will go beyond the status quo by bringing together the observing communities and countries of the Atlantic basin, providing the opportunity to join and support the system. AtlantOS will build upon the coordinated work of the Global Ocean Observing System (GOOS) and the Group on Earth Observations (GEO), two international bodies that support and coordinate global ocean observing. AtlantOS will complement those efforts and offers a new approach to organizing ocean observing at the basin-scale. The new SystemAtlantOS will focus not only on the physics but also the biology, ecology and biogeochemistry of the ocean and seafloor and will enhance new partnerships among between governments, science, civil society and the private sector.